PEMBIAYAAN PT. BANK RAKYAT INDONESIA (PERSERO) TBK CABANG TONDANO TERHADAP SEKTOR PERTANIAN DI KABUPATEN MINAHASA - Omega Bless Ronga; Lyndon R.J. Pangemanan; Grace A.J. Rumagit; Juliana R. Mandei (Universitas Sam Ratulangi, 2015)
ABSTRACTThe aims of the study are to determine the development of BRI credit which has distributed in the agriculture sector, to know and to analyze the development of its credit financing on agriculture and non agriculture, to know about non performing loans at BRI. The research was conducted at PT. Bank Rakyat Indonesia (Persero) Tbk specifically at Tondano Minahasa District Branch. In this research only on certain BRI unit that ditributes credits to agriculture sector. Those units are unit BRI Langowan, unit BRI Kawangkoan, unit BRI Tondano, and unit BRI Sonder. The data were analyzed by using quantitative and qualitative descriptive data analysis then were presented in Tables. The results show that the financing plan and credit that distributed by BRI branch in Tondano to agriculture sector in Minahasa is increasing from year to year. It can be seen from the financing achievement provided by BRI is greater than the BRI financing target. The development of BRI agriculture and non agriculture financing has experienced of increasing from 2011 to 2013 through BRI credit such as KUR Mikro and KKP-E. BRI has faced credit problems when the time of credit repayment in which the NPL of non agriculture is 50% as for agriculture sector NPL is only 20%. This may happen because of the lenders could not pay their debts.